2018
DOI: 10.1186/s13089-018-0096-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of heart, lung and diaphragmatic ultrasound on prediction of failed extubation from mechanical ventilation in critically ill patients: a prospective observational pilot study

Abstract: BackgroundFailed extubation from mechanical ventilation in critically ill patients is multifactorial, complex and not well understood. We aimed to identify whether combined transthoracic echocardiography, lung and diaphragmatic ultrasound can predict extubation failure in critically ill patients.ResultsFifty-three participants who were intubated > 48 h and deemed by the treating intensivist ready for extubation underwent a 60-min pre-extubation weaning trial (pressure support ≤ 10 cmH2O and positive end expira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 45 publications
2
29
0
1
Order By: Relevance
“…LUS can aid to assess lung water volume overload in a timely manner and non-invasive, quick way to predict post-extubation failure. 9 LUS finding in our study prior to extubation was normal with no other associated pathological signs. Mean LUS score before and after extubation was highly significant except in one failed extubation case.…”
Section: Resultssupporting
confidence: 50%
“…LUS can aid to assess lung water volume overload in a timely manner and non-invasive, quick way to predict post-extubation failure. 9 LUS finding in our study prior to extubation was normal with no other associated pathological signs. Mean LUS score before and after extubation was highly significant except in one failed extubation case.…”
Section: Resultssupporting
confidence: 50%
“…The association between lung de-recruitment and weaning failure was emphasized by Jabaudon et al who found a loss of aerated lung mass to be the only predictor of weaning failure [13]. In addition to corroborating all of the above, Haji et al also pointed out the clinical relevance of LUS examination in predicting weaning outcome [14].…”
Section: Lung Ultrasound Score (Lus)mentioning
confidence: 89%
“…Bouhemad showed to be accurate the use of the lung ultrasound reaeration score for the use of antibiotics in ventilator-associated pneumonia [ 60 ]. Haji et al showed parameters lung (loss of aeration score of the left and right anterior and lateral regions) and parameters cardiac through diastolic dysfunction (left atrial area, E/E′, interatrial septal rightward fixed curvature) to help predict failed extubation [ 49 ]. Echocardiography should be further explored in this population because the risk of swings and changes in heart-lung interaction can influence the success of weaning from MV [ 38 , 78 ].…”
Section: Potential Methods For Predicting MV Weaning In Ardsmentioning
confidence: 99%